2017
DOI: 10.4236/ojn.2017.711096
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Integrating Concept Mapping in Nursing Education: An Integrative Review

Abstract: Purpose: The purpose of this review was to investigate the current state of knowledge about the effectiveness of concept mapping in nursing education. Methods: An integrative review adapted a systematic approach. Also, after an extensive search from different databases, ten articles were retrieved and fully reviewed. Results: The ten reviewed articles were adopted quantitative, qualitative, and mixed method designs. Four main themes were identified: 1) from passive to active learners, 2) establishing new knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…These finding is in the same line with BouJaoude & Attieh (2008) [48] who said that the result of their study showed that the total scores on the concept map showed a significant correlation with the scores on the application and level items on the posttest. In addition to Khrais & Saleh (2017) [49] who said that by using concept map assessment rubric, a quasi-experimental study for 102 nursing students revealed that concept mapping is directly correlated with students' abilities to solve problem independently.…”
Section: Discussionmentioning
confidence: 99%
“…These finding is in the same line with BouJaoude & Attieh (2008) [48] who said that the result of their study showed that the total scores on the concept map showed a significant correlation with the scores on the application and level items on the posttest. In addition to Khrais & Saleh (2017) [49] who said that by using concept map assessment rubric, a quasi-experimental study for 102 nursing students revealed that concept mapping is directly correlated with students' abilities to solve problem independently.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a method that has been started to be used since the early 1980s, it was first used in nursing education in 1992 (Daley, Morgan, & Beman, 2016). This technique is used in clinical applications, case presentations and lectures in nursing education (Bayindir et al, 2015;Khrais & Saleh, 2017;Trevisani et al, 2016;Uslu et al, 2013).…”
Section: Concept Mapmentioning
confidence: 99%
“…The concept map is an innovative method that will facilitate students' learning process (El-Hay, El Mezayen, & Ahmed, 2018;Rosciano, 2015). It should be supported by instructors and students as a learning method (Jaafarpour, Aazami, & Mozafari, 2016;Khrais & Saleh, 2017). "The CMap Tools Concept" and "Mind Map Program" are also available for creating concept maps.…”
Section: Concept Mapmentioning
confidence: 99%
“…On the other hand, the process of constructing concept maps is considered to be a tedious task as a reasonable amount of time and effort are consumed in analyzing the different associations among the concepts to generate a concept map of good quality (Khrais & Saleh, 2017). Due to the limitations, some researches such as Atapattu et al (2017), , Huang, Yang, & Lawrence (2015), , Zubrinic, Kalpic, & Milicevic (2012) and Chen & Sue (2013), have proposed intelligent tools and algorithms to automate this process and generate accurate maps in comparatively lesser time and efforts.…”
Section: Figure 1 a Concept Map By Joseph Novakmentioning
confidence: 99%